1985
DOI: 10.3354/meps024243
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient cycling in a microflagellate food chain: II. Population dynamics and carbon cycling

Abstract: Carbon cycling in a 3-member food web containing a diatom (Phaeodactylurn tricornutum), bacteria, and a herbivorous/bacterivorous microflagellate (Paraphysornonas jmperforata) was examined. Ingestion of prey by the microflagellate was the primary mechanism for remineralization of particulate organic material. Approximately 65 % of the particulate organic carbon (POC) initially present was lost over the course of the 8 d experiments in cultures containing microflagellates. No significant increase in remineraliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
85
2

Year Published

1986
1986
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(100 citation statements)
references
References 6 publications
13
85
2
Order By: Relevance
“…These low ingestion rates were, in large part, due to the relatively low phosphorus cell quotas of the Plimited prey (Table l ) . As reported earlier, microflagellate clearance (m1 cell-' d-') and specific growth rates (d-') were not greatly affected by prey nutritional state (Table 1 and Caron et al 1985). Phosphorus excretion under these conditions did not begin until the transition phase, and then at a very low rate (0.1 to 0.2 pg P cell-' d-l); even lower excretion rates occurred during the stationary period (Table 3).…”
Section: Phosphorus Excretion By Microflagellatessupporting
confidence: 78%
See 1 more Smart Citation
“…These low ingestion rates were, in large part, due to the relatively low phosphorus cell quotas of the Plimited prey (Table l ) . As reported earlier, microflagellate clearance (m1 cell-' d-') and specific growth rates (d-') were not greatly affected by prey nutritional state (Table 1 and Caron et al 1985). Phosphorus excretion under these conditions did not begin until the transition phase, and then at a very low rate (0.1 to 0.2 pg P cell-' d-l); even lower excretion rates occurred during the stationary period (Table 3).…”
Section: Phosphorus Excretion By Microflagellatessupporting
confidence: 78%
“…In fact, in the current experiments the average gross growth efficiency of Paraphysomonas jmperforata was 44 + 11 %, based on cell volume . Caron et al (1985) also found that respiration and, to a lesser extent, release of dissolved organic carbon by P. imperforata was tightly coupled to nutrient regeneration. Thus, as discussed previously , the marine microbial food web must be exceedingly complex with, at least, several grazing steps to achieve the high (90+ O/O) regeneration efficiencies attributed to microzooplankton by Eppley & Peterson (1979) and Jackson (1979).…”
Section: Dark Lncubat/o/v P€r/od (Days)mentioning
confidence: 85%
“…this range, or higher, are frequently used in food-web models, resulting in considerable potential for ciliate production. However, reported values of K, for planktonic oligotrich ciliates actually range between 8 and 76% (Caron et al 1990, extracted from table 2). Because inferences about food-web structure are highly sensitive to this coefficient, it bears further experimental attention.…”
mentioning
confidence: 99%
“…Given the natural variability of ciliate biovolume (Hamilton and Preslan 1969;Fenchel and Jonsson 1988) and that of some prey items of ciliates (Ammerman et al 1984;Caron et al 1985), biovolume can be an uncertain currency for such calculations. In addition to natural variations in cell size, fixatives and preservatives can cause shrinkage of ciliates (Choi and Stoecker 1989), microflagellates (Klein Breteler 1985), and bacteria, further calling into question volume-specific estimates of K,.…”
mentioning
confidence: 99%
“…Heterotrophic bacteria in aquatic ecosystems depend on nutrients and dissolved organic matter as resources, and bacteria are in turn preyed upon by protozoan and metazoan plankton Caron et al 1985;Azam 1998). As such, bacteria channel dissolved inorganic and organic matter into higher trophic levels.…”
mentioning
confidence: 99%